2015
DOI: 10.1038/srep08155
|View full text |Cite
|
Sign up to set email alerts
|

SMK-17, a MEK1/2-specific inhibitor, selectively induces apoptosis in β-catenin-mutated tumors

Abstract: Although clinical studies have evaluated several MEK1/2 inhibitors, it is unlikely that MEK1/2 inhibitors will be studied clinically. BRAF mutations have been proposed as a responder marker of MEK1/2 inhibitors in a preclinical study. However, current clinical approaches focusing on BRAF mutations have shown only moderate sensitivity of MEK1/2 inhibitors. This has led to insufficient support for their promoted clinical adoption. Further characterization of tumors sensitive to MEK inhibitors holds great promise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 43 publications
3
9
0
Order By: Relevance
“…APC is a negative regulator of the Wnt signaling pathway, and the truncated mutations of APC fail to form a scaffold for the destruction complex, leading to stabilized β‐catenin and an aberrantly activated Wnt signaling pathway . Moreover, stimulation of β‐catenin wild type A375 cells with Wnt‐3a enhanced the ability of SMK‐17 to induce apoptosis in β‐catenin wild type A375 cells, as previously reported . However, nonactin failed to induce apoptosis in A375 cells even after stimulation with Wnt‐3a (Fig.…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…APC is a negative regulator of the Wnt signaling pathway, and the truncated mutations of APC fail to form a scaffold for the destruction complex, leading to stabilized β‐catenin and an aberrantly activated Wnt signaling pathway . Moreover, stimulation of β‐catenin wild type A375 cells with Wnt‐3a enhanced the ability of SMK‐17 to induce apoptosis in β‐catenin wild type A375 cells, as previously reported . However, nonactin failed to induce apoptosis in A375 cells even after stimulation with Wnt‐3a (Fig.…”
Section: Discussionsupporting
confidence: 76%
“…We have previously reported that MEK1/2 inhibitors induce cell growth arrest in β‐catenin wild type tumor cell lines, whereas they induce apoptosis in β‐catenin mutant tumor cell lines in vitro . Furthermore, we have reported that a MEK inhibitor alone could induce significant tumor regression in β‐catenin‐mutant xenograft models . These findings support the clinical use of MEK inhibitors as single agents for patients with colorectal carcinoma who carry active β‐catenin mutations.…”
supporting
confidence: 65%
See 3 more Smart Citations